Sistem Informasi Sekolah Menengah Pertama Negeri 33 Rejang Lebong - Adzan Ansyori; Anisya Sonita; Surya Ade Saputra (UNIVED Press, 2022)
ABSTRACT As technology develops, information technology requires quality improvement and service mechanisms, one example of which is the school information system website. Human Resources produced from the world of education must provide information facilities and contribute to building technology in the field of education itself, so that it can present effective and efficient information for the entire academic community and the wider community. The research method used is the system development method, method The system development used is Rapid Application Development (RAD) where RAD uses an object-oriented approach for system development. This method aims to shorten the time in planning, designing and implementing a system repeatedly. The result of designing an information system website is the creation of an information system website for the 33rd State Junior High School in Rejang Lebong which is easily accessible by the academic community and the wider community. The conclusion from the information system website for SMPN 33 Rejang Lebong is to produce a website that can help process data and provide information about schools that can improve the performance of school equipment effectively and efficiently, as a means of delivering academic information. And it is hoped that further research will pay attention to the level of security and maintenance and improve the quality and credibility of the SMPN 33 Rejang Lebong website KeyWord : Website, RAD, SMPN 33 Rejang lebong.